Trastornos del aprendizaje hiperactividad - Moran Lara, Jessica Alexandra (2016)
The purpose of this research is to know the causes of the student learning disorder hyperactivity disorder, also known as Attention Deficit Hyperactivity Disorder (ADHD), to promote integration in the student who suffers, where the main actor is the teacher who through talks or psychological workshops offered by the institution helps instill inclusive education for better academic and social development of the student, as well as provide proper attention to it. Sometimes the teacher finds it very difficult to work with such students, for their discipline deemed inappropriate and that is where the child is excluded, and therefore this is complicated their environment, making it difficult to concentrate in the work entrusted by his tutor and classroom tasks, for which the teacher must use adequate strategies and techniques to attract their attention and have the child interested in the given academic tasks. It is necessary for both the classroom and tasks the child to pay due attention to good school performance, since it is continuously expanding its instructional setting, the hyperactive child has an inexhaustible energy and teachers must know how to harness that energy, these children are very prominent in the area of technology, and increasingly need to explore more, go at a pace faster than a child who does not suffer hyperactivity therefore has been desirable to use specific methods and techniques (observation, interview, survey) to help us understand the subject of investigation and in turn, strengthen the Teaching Learning Process (TLP) for a process without discrimination because a good strategy will make the child sitting motivated, attracted and interested in what happens in their environment, its educational performance will be much more productive and profitable.